Hubungan antara Self Esteem dengan Problematic Internet Use pada Siswa Sekolah Menengah Atas (SMA) di Sumatera Barat - Anggara, Putri Satya; Aulia, Farah (Lembaga Yasin AlSys, 2025)
This study aims to examine the relationship between self-esteem and problematic internet use (PIU) among high school students in West Sumatra. A correlational quantitative approach was used with purposive sampling. The study involved 357 students who met the criterion of using the internet for more than five hours per day. The research instruments were validated self-esteem and PIU scales. Data were analyzed using the Spearman correlation test. The results showed a significant negative relationship between self-esteem and PIU (r = -0.642; p < 0.05), indicating that the lower the self-esteem, the higher the tendency for students to engage in problematic internet use, and vice versa. These findings suggest that low self-esteem may be a risk factor for uncontrolled internet use behavior. The conclusion of this study is that self-esteem plays an important role in preventing excessive internet use, which can negatively affect students’ psychological well-being. The implications of this study highlight the need for self-esteem enhancement interventions in school guidance and counseling programs to reduce the risk of PIU among adolescents.